2020
DOI: 10.2478/raon-2020-0021
|View full text |Cite
|
Sign up to set email alerts
|

Relation of the chondromalatia patellae to proximal tibial anatomical parameters, assessed with MRI

Abstract: BackgroundMagnetic resonance imaging (MRI) is a non-invasive highly sensitive tool for diagnosing chondromalacia patellae in the early stages. Many studies have evaluated patellar and trochlear morphology with different radiologic indices. We aimed to assess the discriminative power of tibial, patellar, and femoral indices in MRI for chondromalacia patellae.Patients and methods100 cases of chondromalacia, as well as 100 age-matched controls among the patients who underwent knee MRI between February 2017 and Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
0
7
1
1
Order By: Relevance
“…At present, the etiological study of CP is not clear. Most researchers tend relate the biomechanical function disorder of patellofemoral joint due to various factors, such as knee joint trauma, patellofemoral instability, cartilage dystrophy, and so on ( 6 , 12 , 14 ). The abnormal morphology of the patellofemoral joint can destroy the stability of the patellofemoral joint, so that the pressure distribution on the cartilage surface of the patellofemoral joint is not uniform, and the wear and softening of the patellar cartilage are aggravated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, the etiological study of CP is not clear. Most researchers tend relate the biomechanical function disorder of patellofemoral joint due to various factors, such as knee joint trauma, patellofemoral instability, cartilage dystrophy, and so on ( 6 , 12 , 14 ). The abnormal morphology of the patellofemoral joint can destroy the stability of the patellofemoral joint, so that the pressure distribution on the cartilage surface of the patellofemoral joint is not uniform, and the wear and softening of the patellar cartilage are aggravated.…”
Section: Discussionmentioning
confidence: 99%
“…It can display change at the early stage of cartilage degeneration, including irregular signal, fissure, and cartilage thinning. Therefore, it is often used in the early diagnosis of CP ( 6 , 7 ), with an accuracy of 69–97% ( 8 ). The need for MRI, an expensive piece of equipment, and the need for radiologists who specialize in skeletal muscle disease diagnosis contribute to the threshold for diagnosing chondromalacia patellae.…”
Section: Introductionmentioning
confidence: 99%
“…Knee arthroscopy as well as Magnetic Resonance Imaging (MRI) can indicate the extent and degree of tissue damage and decide on further treatment. MRI with a high tissue contrast can detect chondromalacia in the lower stages: signal irregularities, fi ssures and chondral thinning thus leading to earlier diagnosis and treatment [11,13].…”
Section: Diagnosismentioning
confidence: 99%
“…Patellar malalignment may be related to patellar (sub)luxation, dysplasio of the femoral trochlea as well as deformities of proximal tibia anatomical parameters such as: tibial slope, trochlear depth, lateral trochlear inclination, and lateral patellar tilt. According to some authors, articular cartilage damage (ICRS grade 1-4: cartilage softening, cartilage surface fi ssures, cartilage fragmentation, cartilage necrosis) in the region of patellofemoral joint is arthroscopically detected in 71% patients with different types of knee trauma, such as: menisci rupture (46%), anterior cruciate ligament rupture (34%) and recurrent patellar luxation (15%) Cartilage damage stimulates transition of proinfl ammatory cytokines to cartilage as well as the local metabolic changes; chondrocytes increase the secretion of proteglycans and collagen, enzymatic tissue degradation accelerates so the subchondral bone might terminally be affected with sclerosis, while cartilage becomes softer [6,7,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Duran S et al [10] and Tuna BK et al [5] were reported that there was an association between abnormal trochlear morphology and chondromalacia patella in women. In addition, the study of Tabary M et al showed that the patellar height might be an important factor in the severity of chondromalacia patella [11]. In the study by Deniz Özel, both patella alta and patella baja were found to be related to chondromalacia patella, and the modi ed Insall-Salvati index ratio was the best indicator to de ne patella alta [12].…”
Section: Introductionmentioning
confidence: 96%